Dynamic crosstalk between Tspan4+ macrophage subsets and MSCs via migrasomes orchestrates fracture repair - Zhang, Siyu; Wang, Mengci; Kutibiding, Abudurexiti; Liu, Dandan; Manafu, Tuersunnayi; Zhao, Wen; Yang, Yi (Frontiers in Cell and Developmental Biology, 2026)
BackgroundThe cell - cell communication between macrophages and mesenchymal stromal/stem cells (MSCs) holds pivotal importance in the fracture healing process. Considering the intricate nature of the in vivo bone regeneration microenvironment, elucidating the changes in different macrophage subsets within this microenvironment, as well as the cell - cell communication between these subsets and MSCs, is essential for the differentiation, recruitment, and regulation of MSCs. This study was designed to investigate the interactions between diverse macrophage subsets and MSCs during the fracture healing period.MethodsSingle - cell sequencing was utilized to analyze the expression of Tspan4+, Lyve1+, and Mpeg1+ in macrophages during fracture healing, along with the cell - interaction signals with MSCs. It was demonstrated that the cell - interaction signal transduction might be linked to migrasomes. Scratch assays and transwell assays were carried out to assess the migration capacity of MSCs affected by exosomes and migrasomes derived from Tspan4+Mpeg1+ macrophages. Micro-CT and immunofluorescence techniques were employed to observe the impacts of exosomes and migrasomes from 100 μg/mL Tspan4+Mpeg1+ macrophages on femoral fracture healing in mice.ResultsThrough single - cell sequencing, it was ascertained that macrophages highly expressed Tspan4 during the fracture healing process and could be categorized into Tspan4+Lyve1+ macrophages and Tspan4+Mpeg1+ macrophages. By means of cell - communication analysis, Tspan4+Lyve1+ macrophages and Tspan4+Mpeg1+ macrophages were proposed to interact with MSCs via Gas6 - Axl and IL1b - IL1r1, respectively. Collectively, macrophage-derived migrasomes convey IL-1β to MSCs to activate AMPK, thereby enhancing BMSC migration and likely osteogenic priming during fracture repair. These findings identify migrasomes as a previously underappreciated conduit in macrophage–BMSC crosstalk and suggest a vesicle-based strategy to improve fracture healing.